Invasive Thymoma Protruding into the Superior Vena Cava through the Thymic Vein - Ohata, Keiji (Ann Thorac Cardiovasc Surg, 2015)
We report a rare case of protrusion of an invasive thymoma with intraluminal growth through the thymic vein into the superior vena cava (SVC) without direct invasion of the vessel walls. The tumor and left brachiocephalic vein were resected, and the tumor in the SVC was removed with temporal bypass of the right brachiocephalic vein and right auricle. Histopathological finding showed that the thymoma had protruded via a thymic vein. During resection of a thymoma, a detailed examination of thymic vein is necessary to ensure that no tumor tissue remains in the vessels.